The Role of Management Control Systems in Small and Medium Enterprises - Vallabhaneni, Madhulika (2020)
The literature emphasizes importance on the role played by Management Control Systems in organizations. However, there are few empirical and theoretical studies on the role of Management Control Systems in a Small and Medium Enterprise context. Drawing upon the contingency theory, the aim of the study is to contribute to filling this gap by examining the role played by Management Control System’s in Small and Medium Enterprises setting. The study adopted a qualitative approach of conducting semi-structured interviews in the Kingdom of Bahrain during a two-week period. A total of five Semi-structured interviews were carried out to gain insight on the context (internal and external factors/environment) that SMEs are operating in and the Role of MCSs in SMEs. The transcribed (verbatim) interviews were analyzed using the Thematic analysis approach. The Analysis was carried out on the NVivo 12 software. The Research Findings indicate that it is necessary and essential to implement a Management Control System in an SME. The Management Control System has a very important role to play in an SME, but there are certain challenges of implementing an MCS. The results suggest that the design and use of an MCS is contingent upon the internal and external environment that the SME operates in.